Subperiodic, asymptomatic microfilaremia in an adult male from Mysore: A nonendemic area - Sumana M; Jayashree K; Subhash Chandra B; Girish M (Wolters Kluwer Medknow Publications, 2009)
Wuchereria bancrofti is found throughout tropics and subtropics like Asia, Pacific islands, Africa, areas of South America and Caribbean basin. In all these areas, except Pacific islands, microfilaria occurs in the periodic form, in which case the microfilaria are found in large numbers in the peripheral blood during night. In the Pacific islands, they occur in the subperiodic form, i.e., microfilaria are present in the peripheral blood at all times and reach the maximum level of parasitemia in the afternoon. Microfilaria of Wuchereria bancrofti and Brugia malayi occurring in India displays a nocturnal periodicity, appearing in large numbers at night. This is the biological adaptation to the nocturnal biting habits of the vector mosquitoes. The maximum density in blood is reported between 10 PM and 2 AM. Here is a case report of asymptomatic microfilaremia showing subperiodicity, which is very unusual in India.